Synthetic torpor triggers a regulated mechanism in the rat brain, favoring the reversibility of Tau protein hyperphosphorylation - Squarcio, Fabio; Hitrec, Timna; Piscitiello, Emiliana; Cerri, Matteo; Giovannini, Catia; Martelli, Davide; Occhinegro, Alessandra; Taddei, Ludovico; Tupone, Domenico; Amici, Roberto; Luppi, Marco (Frontiers in Physiology, 2023)
Introduction: Hyperphosphorylated Tau protein (PPTau) is the hallmark of tauopathic neurodegeneration. During “synthetic torpor” (ST), a transient hypothermic state which can be induced in rats by the local pharmacological inhibition of the Raphe Pallidus, a reversible brain Tau hyperphosphorylation occurs. The aim of the present study was to elucidate the – as yet unknown – molecular mechanisms underlying this process, at both a cellular and systemic level. Methods: Different phosphorylated forms of Tau and the main cellular factors involved in Tau phospho-regulation were assessed by western blot in the parietal cortex and hippocampus of rats induced in ST, at either the hypothermic nadir or after the recovery of euthermia. Pro- and anti-apoptotic markers, as well as different systemic factors which are involved in natural torpor, were also assessed. Finally, the degree of microglia activation was determined through morphometry. Results: Overall, the results show that ST triggers a regulated biochemical process which can dam PPTau formation and favor its reversibility starting, unexpectedly for a non-hibernator, from the hypothermic nadir. In particular, at the nadir, the glycogen synthase kinase‐β was largely inhibited in both regions, the melatonin plasma levels were significantly increased and the antiapoptotic factor Akt was significantly activated in the hippocampus early after, while a transient neuroinflammation was observed during the recovery period. Discussion: Together, the present data suggest that ST can trigger a previously undescribed latent and regulated physiological process, that is able to cope with brain PPTau formation.